O gesto de anarquia a partir da obra de Giorgio Agamben - Guimarães, Diego (2019)
The central problem that this thesis pursues is the relationship between Giorgio Agamben's work, anarchy and anarchism, based on the hypothesis that Agamben's thought can be taken as anarchic thought. Anarchy is characterized by a situation of non-government, an absence of government over people and relations between people. Anarchism, by adopting anarchy as its starting point, is dedicated, in its theoretical and practical body, above all, to maintain the situations and conditions of non-government, and is dedicated to resisting all forms of government. As resistance to the rule of life is one of the main characteristics of anarchism, such resistance becomes the guiding line in the task of bringing Agamben, anarchy and anarchism closer together. To highlight Agamben's work as characteristically linked to resistance to the rule of life, an approximation is developed between the work of the philosopher and the works of two contemporary French anarchist groups, the Imaginary Party and the Invisible Committee, insofar as these influence Agamben as far as he resorts in his work to essays published in Tiqqun magazine by the Imaginary Party, especially with regard to the concept of bloom developed by this group. Such approach is guided by the development, within the thesis, of the concepts of uprooting and rooting, in their relations with the agambenian concepts of apparatus, exception, naked life, form-of-life and use. Another moment of the investigation is made using commentators who evaluate the possibility of relating Agamben with anarchism and postanarchism, which highlights, as a way of approximation, the agambenian concept of inoperability. Following this path, we analyze works by Agamben in which he develops the concept of inoperability and works in which he addresses the themes of anarchy and anarchism. To clarify the concepts of inoperability, destitution and anarchy, an analysis of the concept of neutralization in its relation with the concept of destruction is performed. Finally, based on the concepts of gesture and posture, thought by Agamben in relation to inoperability, we investigate the gesture of anarchy and the posture of anarchy as ways to expose anarchic potency and resist the rule of life. It is concluded that the initial hypothesis that Agamben's thought can be taken as anarchic thought was corroborated.